ENTREPRENEURIAL SUPPLY CHAIN MANAGEMENT COMPETENCE IN BAMBOO-BASED CREATIVE MICRO-BUSINESSES (Proceeding of SINERGY, 2026)
This study aims to identify the most dominant dimensions of Entrepreneurial Supply Chain Management (SCM) Competence and those requiring improvement within bamboo-based creative micro-enterprises. The research adopts a descriptive quantitative approach involving 66 bamboo artisans in Mekarsari Village, Selaawi District, Garut Regency. Data were analyzed using descriptive statistics (means and standard deviations) to map artisans’ competency levels. The findings indicate strengths in the adoption of appropriate production technologies, employee involvement in continuous improvement, alertness to technological developments, the maintenance of strong relational ties, and proximity to suppliers that reduces lead times. Areas requiring enhancement include the uneven diffusion of product innovation, a shift in technology opportunity orientation from merely operational to strategic, more consistent communication governance, and broader utilization of delivery services, which is currently constrained by damage risk. Practical implications emphasize strengthening innovation orientation and proactiveness through training and mentoring for new product development, improving e-business literacy, refining internal communication mechanisms with employees, and establishing safe logistics Standard Operating Procedures.